The desmoplastic limph node reaction as a prognostic factor of cancer of the tongue and floor of the mouth. - Lehn, Carlos Neutzling; Rapoport, Abrão (São Paulo Medical Journal, 1994)
To determine the prognostic significance of desmoplasia in metastatic lymph nodes of squamous cell carcinoma of the oral tongue and floor of mouth, 37 cases of this disease were studied. Desmoplasia was present in 59,4% of the cases and associated extracapsular spread in 40,5%. The association of desmoplasia with large lymph node involvement occurred in 59,4%. These relationships were statistically significant (p= 0,002 and 0,0069). The results obtained suggest that desmoplasia is a bad prognosis associated factor.